2005
DOI: 10.1038/sj.jhh.1001896
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementing national hypertension guidelines on prevalence and workload in primary care: a population-based survey of older people

Abstract: upon Tyne, UKRecently revised UK and US hypertension guidelines have reduced thresholds for both diagnosis and treatment and differ in their recommendations. We have used data from a random, stratified community-based sample of 4784 people aged 65 years and over to compare the prevalence of treatable hypertension and the potential impact on patients and primary care from using current guidelines. BHS, NICE and JNC7 guidelines were applied to blood pressures obtained from primary care medical records (94%) or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
0
6
0
1
Order By: Relevance
“…It is well known that calcium channel blockers and thiazide diuretics are initial choices for the treatment of elderly hypertensive patients (19,20). Nevertheless, newly developed angiotensin-converting enzyme inhibitors (ACEI) or angiotensin II receptor blockers (ARB) also have clinical benefits in elderly hypertensive patients (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that calcium channel blockers and thiazide diuretics are initial choices for the treatment of elderly hypertensive patients (19,20). Nevertheless, newly developed angiotensin-converting enzyme inhibitors (ACEI) or angiotensin II receptor blockers (ARB) also have clinical benefits in elderly hypertensive patients (21).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the influence of the complications and weighed monthly cost on the ambulatory hypertension cost we performed a one way sensitivity analysis by varying the weighed monthly cost and probability of the hypertension and its complications within the ±30% interval. Abbreviations used: 1 NHIF -National health insurance fund; 2 AH -arterial hypertension; 3 AP -angina pectoris; 4 SCD -sequellae of cerebrovascular disease; 5 HF -heart failure; 6 WMC -weighed monthly cost; 7 AH -arterial hypertension…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Overall, 26.4% of the adult population in 2000 had hypertension and it is expected that 26.1% of women, and 29.2% of men will have this condition by 2025 year worldwide (1). In Europe the hypertension was found to be more prevalent than in USA and Canada and poor controlled (2)(3)(4)(5). Hypertension is a major global economic burden because of an increased risk for cardiovascular events and inadequately controlled high blood pressure raises the medical, economic, and human costs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well known that calcium channel blockers and thiazide diuretics are recommended as the initial choice for elderly hypertensive patients. 32 A recently published clinical study has clearly demonstrated that using newly developed antihypertensive medications have clinical benefit over the older drugs such as betablockers and diuretics in terms of reduction in cardiovascular and cerebrovascular events. 33 Furthermore, newly developed angiotensin-converting enzyme inhibitors or angiotensin receptor blockers also have clinical benefit in elderly hypertensive patients.…”
Section: Antihypertensive Medication In the Elderly: Which Is The Besmentioning
confidence: 99%